An overlap-weighted analysis on the association of constipation symptoms with disease progression and survival in amyotrophic lateral sclerosis: a nested case-control study - Tongyang Niu; Peize Wang; Xiaomeng Zhou; Tingting Liu; Qi Liu; Rui Li; Haitao Yang; Hui Dong; Yaling Liu (Therapeutic Advances in Neurological Disorders)
Background: Amyotrophic lateral sclerosis (ALS) is a rapidly progressing and rare neurodegenerative disease. Therefore, evaluating the risk factors affecting the survival of patients with ALS is crucial. Constipation, a common but overlooked symptom of ALS, can be effectively managed. It is currently unknown whether constipation contributes to the progression and survival of ALS. Objectives: This study aimed to investigate the association between constipation and ALS development and survival using a novel overlap-weighted (OW) method to enhance the robustness and reliability of results. Design: This prospective matching nested case-control (NCC) study was conducted within an ongoing ALS cohort at the Second Hospital of Hebei Medical University. Baseline data were collected from patients meeting the inclusion and exclusion criteria, with constipation as the exposure factor. A 9-month follow-up was conducted, with death as the endpoint event. Methods: We primarily used the OW method in NCC studies to examine the association between constipation and ALS development and survival. Weighted Cox proportional hazards model was used to assess risk factors associated with overall survival. Survival differences between the two groups were analyzed using Kaplan-Meier’s plots and log-rank tests. Finally, the bioinformatic analysis explored common pathways between ALS and constipation. Results: Among the 190 patients included, the prevalence of constipation was 50%. Patients with ALS constipation exhibited faster disease progression ( p  < 0.001), with a positive correlation between constipation severity and progression rate ( r  = 0.356, p  < 0.001). The constipation group had poorer survival before and after OW (log-rank test, p  < 0.0001). In the Cox proportional hazards model of 114 patients, constipation was a risk factor for ALS both before (hazard ratio (HR) = 5.840, 95% confidence interval (CI) = 1.504–22.675, p  = 0.011) and after (HR = 5.271, 95% CI = 1.241–22.379, p  = 0.024) OW. Conclusion: Constipation in individuals with ALS is associated with faster disease progression and reduced survival rates, potentially through the peroxisome proliferator-activated receptor pathway.